Production of singlet oxygen by Ru(dpp(SO3)2)3 incorporated in polyacrylamide PEBBLES - Moreno, Maria João (2003)
Polyacrylamide (PAA) and amine-functionalized PAA (AFPAA) nanoparticles with disulfonated 4,7-diphenyl-1,10-phenantroline ruthenium (Ru(dpp(SO3)2)3) have been prepared. The nanoparticles produced have a hydrodynamic radius of 20-25 nm.